KEHARMONISAN MASYARAKATDITENGAHHOAXCOVID-19DI DESAPASIR PANJANG KECAMATAN MEMPAWAH TIMUR KABUPATEN MEMPAWAH - Saiful, Saiful; Bahari, Yohanes; Ramadhan, Iwan (Universitas Tanjungpura, 2022)
AbstractThis study aims to determine the form of harmony and the efforts made by thecommunity to build harmony in Pasir Panjang Village, Mempawah TimurDistrict, Mempawah Regency. . The method used is a qualitative method withdescriptive analysis. The source of data in this study is the community ofPasir Panjang Village. and the data is the result of observation andsupported by the results of interviews with the people of Pasir PanjangVillage. The results showed that, (1) the form of harmony in the midst of thecovid-19 pandemic hoax in Pasir Panjang Village, Mempawah TimurDistrict, Mempawah Regency had been carried out well, as evidenced by thefact that residents in the village were always doing various activities such ascooking and gathering together during observations. and supported by theresults of interviews with the community. (2) the efforts made by thecommunity to build harmony in the social life of Pasir Panjang Village,Mempawah Timur District, Mempawah Regency have been well established,as evidenced by the discovery of a group of residents who are makingfriendships between residents, where the friendship is in order to establishgood relations between residents and to maintain community harmony at thetime of observation and supported by the results of interviews with thecommunity.Keywords: Harmony, Society, Covid-19